ЖАҢА ТУҒАН ҚОЗЫЛАРДЫҢ ҚАНЫНЫҢ БИОХИМИЯЛЫҚ КӨРСЕТКІШТЕРІНЕ ПРОБИОТИКАЛЫҚ ПРЕПАРАТТЫҢ ӘСЕРІ - Н. Қанатқызы; Д. Сарыбаева; Г. Нургожаева; Г. Кузембекова; Л. Бесембаева; М. Булегенова (Animal Health and Biosafety, 2026)
This study aimed to evaluate the effect of a probiotic preparation on the biochemical and immunological parameters of newborn lambs. The lambs were evenly selected according to body weight and sex and divided into control and experimental groups. The experimental group received the probiotic orally at different doses before colostrum intake. The findings demonstrated a significant improvement in the principal serum biochemical indicators of the probiotic-treated lambs. In particular, increased levels of total protein, albumin, and gamma-globulins reflected enhanced protein synthesis and strengthened humoral immunity. The activities of alanine aminotransferase (ALT), aspartate aminotransferase (AST), and gamma-glutamyltransferase (GGT) remained within physiological ranges, confirming stable liver function. Moreover, the stabilization of glucose, total lipids, and triglycerides indicated optimized carbohydrate and lipid metabolism and more efficient nutrient absorption. The results showed that administering the probiotic during the early neonatal period positively influenced metabolic adaptation in the offspring. In treated lambs, higher total protein fractions suggested intensified plastic processes and favorable conditions for tissue growth and development. Elevated albumin levels supported oncotic pressure stability and improved the transport of biologically active substances, while increased gamma-globulins promoted the formation of passive and active immune responses. The maintenance of enzymatic activity within normal limits indicated preserved hepatocyte integrity and the absence of hepatotoxic effects, reflecting stable detoxification function. Balanced energy metabolism parameters suggested coordinated cellular redox reactions. By normalizing the intestinal microbiocenosis, probiotic microorganisms enhanced nutrient digestion and absorption and increased immunobiological reactivity. Overall, administering probibiotic whey before colostrum intake improved physiological adaptation, growth rate, and resistance in newborn lambs.